Corymbia citriodora: A Valuable Resource from Australian Flora for the Production of Fragrances, Repellents, and Bioactive Compounds. Issue 6 (20th November 2020) - Goodine, Tyler; Oelgemöller, Michael
Abstract: As global chemical manufacturing has historically relied on inexpensive feedstocks from the petrochemical industry, the identification of new naturally derived feedstocks represents an important and sustainable alternative. This review introduces Corymbia citriodora (Hook.) K.D.Hill & L.A.S.Johnson as an attractive renewable resource of natural compounds for organic chemical transformations. Although native to Australia, this plant species is now grown and harvested worldwide. The chemical composition of citriodora oils varies with location, harvesting season and age of leaves. Beyond their historic uses as fragrances or repellents, the more abundant terpenes found in citriodora oils such as citronellal, citronellol, and isopulegol have notable roles in the manufacture of fine chemicals. This review highlights several industrial processes intimately related to the citriodora terpenes, some advances in fragrances and repellents, as well as the use of these terpenes in the most recently reported synthesis of bioactive compounds. Where relevant, processes highlighting the adoption of green chemistry principles are presented and briefly discussed. Abstract : Corymbia citriodora (Hook.) represents an interesting renewable resource of natural compounds for organic chemical transformations. This review highlights several processes of its major constituents for the manufacturing of healthcare and pharmaceutical products.